How do you simplify (x + 3)(x^2 - 4x + 9)?
1 Answer
Explanation:
To simplify this expression, or any expression, a good start would be putting the binomial before the polynomial. This will make it a lot easier to multiply. In this case, it is already this way.
Now we can begin to multiply.
Take the
Then take the
(x + 3)(x^2 - 4x + 9)
(color(blue)(x) + 3)(color(green)(x^2) - 4x + 9) color(orange)(->) x * x^2 color(orange)(->) color(red)(x^3)
(color(blue)(x) + 3)(x^2 color(green)( - 4x) + 9) color(orange)(->) x * -4x color(orange)(->) color(red)(-4x^2)
(color(blue)(x) + 3)(x^2 - 4x color(green)( + 9)) color(orange)(->) x * 9 color(orange)(->) color(red)(9x)
(x color(red)( + 3))(color(green)(x^2) - 4x + 9) color(orange)(->) 3 * x^2 color(orange)(->) color(red)(3x^2)
(x color(red)( + 3))(x^2 color(green)( - 4x) + 9) color(orange)(->) 3 * -4x color(orange)(->) color(red)(-12x)
(x color(red)( + 3))(x^2 - 4x color(green)( + 9)) color(orange)(->) 3 * 9 color(orange)(->) color(red)(27)
Now all we have to do is add the terms that we got and simplify.
x^3 + (-4x^2) + 9x + 3x^2 + (-12x) + 27
x^3 - 4x^2 + 9x + 3x^2 - 12x + 27
x^3 - x^2 - 3x + 27
As you can see, when we simplify our initial expression, we get our answer which is